2019
DOI: 10.29244/jitkt.v11i1.24777
|View full text |Cite
|
Sign up to set email alerts
|

The Model of Macro Debris Transport Before Reclamation and in Existing Condition in Jakarta Bay

Abstract: Jakarta Bay as one of an area with the densest population in Indonesia became one of the highest contamination level waters in the world includes pollution of debris. Reclamation activities in Jakarta Bay will change the water conditions, and will also affect the distribution of debris at sea. Therefore, this study conducted is to determine the movement of the marine macro debris before and on the condition of the existing reclamation island in the Bay of Jakarta. The method used is simulated by the hydrodynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 9 publications
(8 reference statements)
1
10
0
1
Order By: Relevance
“…A previous simulation study showed that tidal moved from the east to the west in the eastern monsoon season. Moreover, plastic litter was higher in the western area, meanwhile in the western monsoon season was vice versa (Jasmin et al, 2019). Our results strengthened this simulation that plastic litter was primarily accumulated in the eastern and western sides instead of in the middle side.…”
Section: Spatial and Temporal Distributionsupporting
confidence: 82%
“…A previous simulation study showed that tidal moved from the east to the west in the eastern monsoon season. Moreover, plastic litter was higher in the western area, meanwhile in the western monsoon season was vice versa (Jasmin et al, 2019). Our results strengthened this simulation that plastic litter was primarily accumulated in the eastern and western sides instead of in the middle side.…”
Section: Spatial and Temporal Distributionsupporting
confidence: 82%
“…The topic of currents and marine macro debris (not only plastic waste) originating from DKI Jakarta has been discussed in previous studies (Jasmin et al, 2019;Jasmin et al, 2020). In his research, the movement of macro debris is divided into the movement of marine macro debris before and after reclamation in Jakarta Bay.…”
Section: Resultsmentioning
confidence: 99%
“…the circulation of ocean currents in Indonesia through most of the East and Southeast Asia region of a country called the Indonesian Throughflow (ITF) [10] to identify a distribution pathway for MD in the oceans can use several methods, most of which research is limited to distribution of MD in an area [11] Some researchers have begun to compare observational data regarding the mass of MD types whose distribution is combined with a model [12]. Based on previous research, there is a hypothetical method used by some researchers to determine the prediction of sources from MD [13] The research can be carried out with different methods, namely in the form of a photometric method that can identify a movement of waste in real-time and cannot predict where the MD will move [14] There is another study using a simple model that utilizes tools in making prediction models from secondary data consisting of wind, current and tidal components, these parameters are factors that have an influence on MD displacement [15]. This observation method can understand the complexity of the movements that occur in waters and other benefits, the data used can be easily accessed and the results obtained are in the form of observational data obtained with minimal costs [16].…”
Section: Movement Of Marine Debrismentioning
confidence: 99%